FACTORS INFLUENCING THE INTENTION TO ADOPT E-WALLET: A REGIONAL DISTRIBUTION PERSPECTIVE IN MALAYSIA - Liew, Vernon; Poh, Phaik See (INTI International University, 2022)
Current mode of cashless payment in Malaysia has reached maturity. E-wallet players has transcended globally, more so with the onset of Covid-19 pandemic that mandated social distancing in early 2020. The renewed and acute need awareness triggered an immense support of e-wallet adoption. Yet, contrary to expectations, only 11% of the total population adopts e-wallet which is one-fifth of total smartphone users in the nation. More than 50% of Malaysia’s revenue comes from taxes. However, substantial revenue is lost through high tax evasion due to less traceable transactions and increased illegal financial outflow. Quenching this curiosity, the research explores factors influencing adoption of e-wallet based on constructs of knowledge, perceived ease of use, perceived usefulness, social influence. Besides, a regional distribution, and the mediating effect of perceived trust between knowledge and intention to adopt e-wallet is examined. Notwithstanding the current technological prevalence in Malaysians’ lifestyle, perceived ease of use and perceived usefulness is purposedly posed as respective independent variables rather than as a mediator as in the Technology Acceptance Model. Using a quantitative approach and purposive sampling technique, data collection is engineered to have a prerequisite of minimum 50 respondents per region. Based on parameters of two tailed test with confidence interval of 95% (significance level 0.05), a total of 400 responses were analysed via SmartPLS with PLS-SEM algorithm. Knowledge, perceived ease of use, perceived usefulness, and the mediating effect of perceived trust on knowledge were found significant. Thus, both the daily performance improvement and effort to manoeuvre e-wallet are essential. Social influence was, however, found insignificant. It could imply that promoting e-wallet adoption through advertisements and peer reviews is not adequate as generally expected. In contrary, enhancing user experience of the e-wallet adopters in terms of ease of use and usefulness is the ultimate key. Regional distribution findings showed that Northern Region (Perlis, Kedah, Penang, and Perak) has the highest e-wallet adoption rate of 94.4%, followed closely by Central Region (Selangor, Federal Territory of Kuala Lumpur, and Putrajaya) at 92.3%. Reminiscing upon a current launch of e-Tunai (e-cash) at Penang at time of the study, practical knowledge is found to be impactful in influencing the intention to adopt e-wallet. As such, opportunities are abundant for relevant stakeholders to strategize and enhance e-wallet adoption among the public as well as the under-served community.